Polyhydrido Copper Nanoclusters with a Hollow Icosahedral Core: [Cu30H18{E2P(OR)2}12] (E=S or Se; R=nPr, iPr or iBu). Issue 46 (20th July 2020) - Barik, Subrat Kumar; Huo, Shou‐Chih; Wu, Chun‐Yen; Chiu, Tzu‐Hao; Liao, Jian‐Hong; Wang, Xiaoping; Kahlal, Samia; Saillard, Jean‐Yves; Liu, C. W.
Abstract: Although atomically precise polyhydrido copper nanoclusters are of prime interest for a variety of applications, they have so far remained scarce. Herein, this work describes the synthesis of a dithiophosphate‐protected copper(I) hydride‐rich nanocluster (NC), [Cu30 H18 {S2 P(O n Pr)2 }12 ] (1H ), fully characterized by various spectroscopic methods and single‐crystal X‐ray diffraction. The X‐ray structure of 1H reveals an unprecedented central Cu12 hollow icosahedron. Six faces of this icosahedron are capped by Cu3 triangles, the whole Cu30 core being wrapped by twelve dithiophosphate ligands and the whole cluster has ideal S 6 symmetry. The locations of the 18 hydrides in 1H were ascertained by a single‐crystal neutron diffraction study. They are composed of three types: capping μ3 ‐H, interstitial μ4 ‐H (seesaw) and μ5 ‐H ligands (square pyramidal), in good agreement with the DFT simulations. The numbers of hydrides and ligand resonances in the 1 H NMR spectrum of 1H are in line with their coordination environment in the solid state, retaining the S 6 symmetry in solution. Furthermore, two new Se‐protected polyhydrido copper nanoclusters, [Cu30 H18 {Se2 P(OR)2 }12 ] (2H : R= i Pr 3H : R= i Bu) were synthesized from their sulfur relative 1H via ligand displacement reaction and their X‐ray structures feature the exceptional case where both the NC shape and size are fully conserved during the course of ligand exchange. DFT and TD‐DFT calculations allow understanding the bonding and optical properties of clusters 1H –3H . In addition, the reaction of 1H with [Pd(PPh3 )2 Cl2 ] in the presence of terminal alkynes led to the formation of new bimetallic Cu−Pd alloy clusters [PdCu14 H2 {S2 P(O n Pr)2 }6 (C≡CR)6 ] (4 : R=Ph; 5 : R= C6 H4 F). Abstract : An atomically and structurally precise polyhydrido copper nanocluster [Cu30 H18 {S2 P(O n Pr)2 }12 ] which embodied an unprecedented inner hollow Cu12 icosahedron core has been isolated and fully characterized by single‐crystal neutron diffraction analysis; while existence of Ag12 and Au12 icosahedra have reported in the year 2013 and 2019, respectively.